An efficient one-pot and solvent-free synthesis of chromeno[2,3-d] pyrimidine derivatives: Microwave assisted reaction - Zonouzi, Afsaneh; Biniaza, Mojtaba; Mirzazadeh, Roghieh; Talebi, Merzieh; Ng, Seik Weng (The Japan Institute of Heterocyclic Chemistry, 2010)
An efficient synthesis of some new chromeno[2,3-d]pyrimidine derivatives has been described by a solvent-free, multi-component reaction in fairly high yields.